The impact of re-engineering to achieve effective performance level of Ministry of electricity operations/an applied study of process reengineering clean solar cells - البياتي, فائز غازي; فهد, جبار قاسم (Journal of Economics and Administrative Sciences, 2013)
The study is dealing with an application reengineering process clean solar cells in the Ministry of electricity,  as aimed at the possibility of the applicability and impact of re-engineering to achieve the level of performance of the Ministry's operations, with the application of the cleaning process  solar cells, developed, improved and found a correlation, statistically significant effect between variable re-engineering and performance as well as the application of process reengineering clean solar cells:1- Before the re-engineering process the total time for cleaning up and solar cell 20 minutes and number of columns performed per day 24 columns and total  columns750 which were completed per month that reached 7,500,000 dinar monthly as a total cost. 2- Before the re-engineering process the total time for cleaning up and solar cell 6 minutes and number of columns performed per day 80 columns and total  columns2400 which were completed per month that reached 750,000 dinar monthly as a total cost. The most important recommendations of the Ministry of electricity must adopt a reengineering process to address all the problems confronting them by forming teams, training and development of employees to access the best ways to improve operations.